COVID-19 outbreak rates and infection attack rates associated with the workplace: a descriptive epidemiological study. Issue 7 (18th July 2022) - Chen, Yiqun; Aldridge, Timothy; Ferraro, Claire; Khaw, Fu-Meng
Abstract : Objectives: A large number of COVID-19 outbreaks/clusters have been reported in a variety of workplace settings since the start of the pandemic but the rate of outbreak occurrence in the workplace has not previously been assessed. The objectives of this paper are to identify the geographical areas and industrial sectors with a high rate of outbreaks of COVID-19 and to compare infection attack rates by enterprise size and sector in England. Methods: Public Health England (PHE) HPZone data on COVID-19 outbreaks in workplaces, between 18 May and 12 October 2020, were analysed. The workplace outbreak rates by region and sector were calculated, using National Population Database (NPD) with the total number of workplaces as the denominator. The infection attack rates were calculated by enterprise size and sector using PHE Situations of Interest data with the number of test-confirmed COVID-19 cases in a workplace outbreak as the numerator and using NPD data with the number employed in that workplace as the denominator. Results: The highest attack rate was for outbreaks in close contact services (median 16.5%), followed by outbreaks in restaurants and catering (median 10.2%), and in manufacturers and packers of non-food products (median 6.7%). The overall outbreak rate was 66 per 100 000 workplaces. Of the nine English regions, the North West had the highest workplace outbreak rate (155 per 100 000 workplaces). Of the industrial sectors, manufacturers and packers of food had the highest outbreak rate (1672 per 100 000), which was consistent across seven of the regions. In addition, high outbreak rates in warehouses were observed in the East Midlands and the North West. Conclusions: Early identification of geographical regions and industrial sectors with higher rates of COVID-19 workplace outbreaks can inform interventions to limit transmission of SARS-CoV-2.